2010
DOI: 10.1016/j.matbio.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Dentin sialophosphoprotein (DSPP) is cleaved into its two natural dentin matrix products by three isoforms of bone morphogenetic protein-1 (BMP1)

Abstract: The protease that cleaves the most abundant non-collagenous protein of dentin matrix, dentin sialophosphoprotein (DSPP), into its two final dentin matrix products, dentin sialoprotein (DSP) and dentin phosphoprotein (DPP), has not been directly identified. In this study, full-length recombinant mouse DSPP was made for the first time in furin-deficient mammalian LoVo cells and used to test the ability of three different isoforms of one candidate protease, bone morphogenetic protein-1 (BMP1) to cleave DSPP at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 56 publications
4
82
0
1
Order By: Relevance
“…Immediately after its synthesis, DSPP is cleaved into DSP and DPP. BMP1, MMP2, and MMP20 have been implicated in the proteolytic process (Yamakoshi et al 2006;von Marschall and Fisher 2010). In this study, we demonstrate that the DSPP gene is essential for the formation of mineralized tissues of the dentalcraniofacial complex.…”
Section: Discussionsupporting
confidence: 50%
“…Immediately after its synthesis, DSPP is cleaved into DSP and DPP. BMP1, MMP2, and MMP20 have been implicated in the proteolytic process (Yamakoshi et al 2006;von Marschall and Fisher 2010). In this study, we demonstrate that the DSPP gene is essential for the formation of mineralized tissues of the dentalcraniofacial complex.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast, He et al (28) showed that high concentrations of sFRP-2 inhibited the cleavage of a fluorogenic peptide and of procollagen I by human BMP-1, and using a similar model, they concluded that direct injection of sFRP-2 in the infracted heart could inhibit fibrosis and improve cardiac function. Finally, a third study from von Marschall et al (29) found that sFRP-2 had no effect on the procollagen-C-proteinase activity of BMP-1.…”
Section: Bone Morphogenetic Protein-1 (Bmp-1)mentioning
confidence: 95%
“…Attempting to explain the apparently contradictory observations of decreased fibrosis in sFRP2-null mice (97) and decreased fibrosis upon injection of sFRP2 into rat heart with MI, He et al (98) suggested that reduced MI fibrosis in sFRP2-null mice may result from apoptotic loss of fibrogenic cells due to loss of sFRP2 anti-apoptotic activity. A third study reported no effect of sFRP2 on the in vitro pCP activity of BMP1 or mTLD (61).…”
Section: Secreted Frizzled-related Proteins (Sfrps)mentioning
confidence: 96%
“…Both are secreted as zymogens that are activated by B/TPs via cleavage of prodomains (59,60). Dentin matrix protein 1 (DMP1) and DSPP (dentin sialophosphoprotein), SIBLING family members, are highly acidic proteins that can be cleaved by B/TPs to produce fragments involved in initiating mineralization of hard tissues (61,62). Observations that DMP1-processing activity is decreased in cells null for BMP1, mTLD, and mTLL1 (62) and that expression of both BMP1 and DMP1 increases coincident with mineralization (63) are supportive of the physiological relevance for B/TP cleavage of DMP1.…”
Section: Non-collagenous Ecm-related Proteinsmentioning
confidence: 99%